Guidelines on the management of irritable bowel syndrome - Anna Pietrzak; Barbara Skrzydło-Radomańska; Agata Mulak; Michał Lipiński; Ewa Małecka-Panas; Jarosław Reguła; Grażyna Rydzewska (Gastroenterology Review)
In memory of Professor Witold Bartnik